PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL PADA DINAS PERHUBUNGAN KABUPATEN PASER - Syarifah, Noor; Darmawan, Dedi; Azis, Syamsuddin (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2023)
This research aims to analyze the influence of motivation and work discipline on the performance of Civil Servants (PNS) in the Paser Regency Transportation Service. Data was obtained from 67 civil servant respondents via questionnaires, and multiple regression analysis using SPSS 20 was carried out. The results of the analysis show that there is a positive relationship between motivation (X1) and work discipline (X2) and civil servant performance (Y), with the regression formula Y = 0.490 + 0.560X1 + 0.289X2. The coefficient of determination (R2) is 51.9%, indicating the contribution of motivation and work discipline variables to civil servant performance, while 48.1% is influenced by other factors. The F test shows the significance of the relationship together, with H0 rejected. Partially, motivation (X1) and work discipline (X2) each have a significant effect on civil servant performance. Motivation (X1) is the dominant variable with the largest t-count value (4.374). Thus, the hypothesis that motivation (X1) partially has a dominant influence on the performance of civil servants in the Paser Regency Transportation Service can be accepted based on the results of this research.